The Effect of the Alternative Evaluation Strategy on the Achievement of Fourth-Grade Female Science Students in the Subject of Biology (Journal Of Educational and Psychological Researches, 2023)
AbstractThe aim of the current research is to identify the Effect of the alternative evaluation strategy on the achievement of fourth-grade female students in the subject of biology. The researchers adopted the zero hypothesis to prove the research objectives, which is there is no statistically significant difference at the level (0.05) between the average scores of the experimental group who study according to the alternative evaluation strategy and the average scores of the control group who study in accordance with the traditional method. The researchers selected the experimental partial adjustment design of the experimental and control groups with the post-test. The researchers intentionally selected (Al-fedaa  prep school for girls) to represent the research community that identified fourth-grade female students in the government schools of the Baghdad Governorate Education Directorate/Second Pavement for the academic year 2021/2022. The researchers randomly selected the two research groups from a total of four adjacent and converging divisions with the number of female students, group (a) experimental group (50) students and group (b) control group (49) students. The two research groups were tested based on the time age of female students was calculated by months, the previous knowledge test, and the IQ test. The scientific material is defined by the following: the first six chapters from the Biology Book of Fourth Grade Science. A behavioral objective (157) has been formulated based on Bloom's classification of the cognitive field of the six levels (remembrance, assimilation, application, analysis, composition, evaluation) over the course of classes during the trial period of 10 weeks. Plans have been prepared to teach the experimental group according to the alternative evaluation strategy and the control group according to the usual method. The study tools of the achievement test have been prepared to consist of (50) items (40 substantive items and 10 article items). Students' answers were corrected and statistically processed using the SPSS statistical pouch. The results showed that there are statistically significant differences at (0.05) level between the average scores of the students of the two research groups in favor of the experimental group in the achievement test at (48.120). The researcher recommended teaching biology by relying on the alternative assessment strategy that affected the achievement of the experimental group students for the better. Teaching procedures using the alternative assessment strategy are consistent with the modern trends of education in making students the focus of the learning process.